The Community Structure Of Macrozoobenthos In Intertidal Zone Of Topang Island Meranti Islands Regency Riau Province - Joromun Rumapea; Thamrin '; Mubarak ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted in December 2013 in the intertidal zone of Topang Island of Meranti Islands regency in Riau Province. This study aims was to determine the community structure of the intertidal zone macrozoobenthos in Topang Island. The method used was a survey to determine the location of the study which consisted of 7 and 3 point sampling station. Macrozoobenthos samples were taken and analyzed in a laboratory of marine biology.The result showed that, the macrozoobenthos in the study site consisted of 18 species belonging to 4 classes. Macrozoobenthos density in the study area varies where the station the highest was of stastion two (II), and the lowest at station VI. Based on the value of diversity index (H ') macrozoobenthos in the study area were at moderate meaning no dominant species and the distribution was at uniformity.Key Words : Intertidal Zone, Macrozoobenthos, Structure Community